Optimized Whole-Genome Amplification Strategy for Extremely AT-Biased Template. - Oyola, S; Manske, M; Campino, S; Claessens, A; Hamilton, W; Kekre, M; Drury, E; Mead, D; Gu, Y; Miles, A; MacInnis, B; Newbold, C; et al. (2014)
Pathogen genome sequencing directly from clinical samples is quickly gaining importance in genetic and medical research studies. However, low DNA yield from blood-borne pathogens is often a limiting factor. The problem worsens in extremely base-biased genomes such as the AT-rich Plasmodium falciparum. We present a strategy for whole-genome amplification (WGA) of low-yield samples from P. falciparum prior to short-read sequencing. We have developed WGA conditions that incorporate tetramethylammonium chloride for improved amplification and coverage of AT-rich regions of the genome. We show that this method reduces amplification bias and chimera formation. Our data show that this method is suitable for as low as 10 pg input DNA, and offers the possibility of sequencing the parasite genome from small blood samples.